AKHLAK ANAK DALAM KITAB TARBIYAH WAL AKHLAK KARYA YAK’UB FAAM - Nisa, Choirun; Fikriya, Kinanthi Nur; Subakti, Amin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Education and morals are two main components that cannot be separated and are interrelated, because they both have a major role in shaping human character in the future. If moral education can be implemented well, all human activities will not be in vain and the goal of moral education, changing attitudes from bad to good, can be optimal. The aim of writing this scientific work is to find out how to build good morals through moral education. This research uses a library method by collecting several books, journals, articles and other related matters to be used as reference material. Meanwhile, for data analysis, content analysis is used. This research produced the following findings: 1) the home and school environment must be improved so that children can focus and participate actively in life, 2) the main and first moral education can start from home or family life towards individual formation, 3) How to improve mental health children and avoiding negative morals can be through learning Islamic worship, 4) Preparing children to consider their rights and obligations in the home environment, 5) Parents can give children the freedom to develop their abilities and desires without restrictions or coercion. So that the best character or morals will be created. Research on the study of children's morals in the book Tarbiyah wal Akhlak by Yak'ub Faam has very broad implications, both in the context of Islamic education, developing children's character, and understanding the thinking of classical scholars. The implications of this research are theoretical, practical and policy implications.